Self‐reported accidental allergic reactions among patients with challenge‐verified food allergy - Sebastian Vigand Svendsen; Annemarie Schaeffer Senders; Athamaica Ruiz Oropeza; Annmarie Lassen; Carsten Bindslev‐Jensen; Charlotte G. Mortz (Clinical and Translational Allergy, 2025)
Abstract Background Food allergy affects up to 6% of the population and emergency department visits due to accidental food‐allergic reactions are increasing. This study evaluated accidental allergic reactions outside the hospital and the number of hospitalizations in food allergic patients as well as the pattern before and after the diagnosis of food allergy by oral food challenge (OFC). Methods An electronic questionnaire concerning accidental allergic reactions was sent to 785 patients with challenge verified peanuts, hazelnuts, cow's milk and/or hen's egg allergies at the Allergy Centre, Odense University Hospital, Denmark. Results In total, 51% (402/785) responded. Among the 357 who reported at least one accidental allergic reaction, 51.5% (184/357) reported a total of six or less reactions, whereas 22.4% (80/357) had experienced a total of ≥21 reactions. Skin symptoms were commonly reported by children/adolescents (n = 277), whereas symptoms from all other organ systems were more frequently reported by adults (n = 80). In total, 61.6% (220/357) experienced at least one accidental allergic reaction, requiring immediate medical attention, which decreased from 77.3% (170/220) before to 55% (121/220) after establishment of the food allergy diagnosis by OFC. A concomitant proportional increase in the number of hospitalizations was identified (63.5% (108/170) to 72.7% (88/121)). Limitations: We had no exact data on the timing of the accidental allergic reactions for the individual allergens. Conclusion Accidental food‐allergic reactions are common and often severe. After the diagnostic OFC, the number of patients with reactions decreased, and the proportion of hospitalizations increased, indicating improved disease and healthcare management.